An Integrative Model of Online/Website Experience: Structural Modelling Approach (Case: Kampung Tarung) - Radeswandri, Radeswandri; Ginting, Ginta (Anotero Lembaga Scientific Pekanbaru, 2025)
This study develops a model using the concept of variable flow based on the limited results of empirical studies regarding online/web experience on strategic aspects that require a theory-based conceptual framework. This model can support the practical strategy to develop tourism sector (Case Kampung Tarung Sumba). Flow variables in this modeling use 3 stages, starting from independent variables (interactivity, usability, connectedness, challenge, skill, telepresence, perceived benefit), component variables (functionality, psychological, content/marketing) and outcome variables (satisfaction, trust and behavior). The unit of analysis is website users of various tourist destinations based on local culture and traditions, with a total of 364 respondents. Data were analyzed using Structural Modeling Approach (SEM-LISREL). The research model can prove most of the hypothesis testing as many as 15 of the 19 proposed hypotheses. The modeling in this study can be declared valid to be developed in the next research. There are 4 hypothesis tests that show insignificant results, namely: 1) the effect of connectedness on functionality; 2) the influence of content on behavioral intention; 3) psychological influence on trust and 4) influence of skill on psychology. For the development of future research, it is necessary to develop a more comprehensive